Synthesis and evaluation of pantothenic acid analogues as potential inhibitors of malaria parasites and bacteria - Jana, Collins Edward (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc (Biochemistry))--Stellenbosch University, 2011.